Minimized preoperative interventions and delayed surgery affect survival in congenital diaphragmatic hernia - Bakal, Ünal; Özel, Kerem; Kazez, Ahmet (My University, 2008)
Aim: Mortality rates are still high in congenital diaphragmatic hernia (CDH). In this study, we aimed to evaluate the factors affecting survival in patients operated for newborn CDH. Material and Method: Medical records of patients operated for CDH between 1997 and 2007 were reviewed retrospectively. Demographic data, maternal age, first intubation time, age at operation, waiting period between diagnosis and operation, postoperative intubation, sedation, thoracic drainage and hospitalization times, defect sizes, intraoperative findings, early and late complications and outcome were noted. Patients were grouped as referred or inborn patients and all data were compared using Mann-Whitney U test. Results: Total of 29 patients, 15 of whom were newborns, were operated for CDH in our clinic over the last 10 years. Only newborns were included in the study and late presenting cases were excluded. Male-female ratio was 1.1:1, and mother age 27±5.9 years. All the patients were full-term and had >2000 gr birth weight. First intubation time was average 9.9±21.7 hours. Waiting period between diagnosis and operation was 4.5±2.4 days. Age at operation was 7±4.1 days, postoperative intubation period 6.7±9 days, sedation time 6,5±5.1 days and hospitalization time were 15±5,4 days, respectively. A modest ventilator regime was preferred pre and postoperatively in all patients. Except for i.v. infusion, endotracheal care and monitorization, no intervention was done unless necessary. No significant difference was found between patients referred or inborn patients (p>0.05). Survival rate was 86.7% in our series. Mental retardation in I patient, pectus excavatum in 2 patients and portal hypertension due to portal vein thrombosis in 1 patient developed as late term complications. Conclusion: CDH has a high morbidity. High survival rates may be achieved with minimized manipulations and delayed surgery in these patients. Mortality may be adversely affected secondary to excessive medical interventions in these patients.
Azaltilmiş ameliyat öncesi girişimler ve geciktirilmiş cerrahi konjenital diyafram hernisinde sa?kahmi etkilemektedir
Keywords: Congenital diaphragmatic hernia; Survival